Carat USA : an e-mail gaffe and reputational furor (A) - Husack, Daniel (SAGE Knowledge. Cases., 2017)
As Carat USA was in the process of implementing a restructuring plan, a top HR executive accidentally forwarded the communication plan to the entire company via email. The confidential document included the firms messages to employees, clients, vendors and other stakeholders. How can Carat USA recover from the mistake and restore its reputation?